Grasping VR: Presence of Pseudo-Haptic Interface Based Portable Hand Grip System in Immersive Virtual Reality. Issue 7 (20th April 2020) - Kim, Mingyu; Kim, Jinmo; Jeong, Kisung; Kim, Changhun
ABSTRACT: This study proposes a pseudo-haptic interface optimized for a novel portable hand grip haptic system, providing simple and realistic interfaces in various situations using the hand grips of users in immersive virtual reality. The proposed haptic system accurately determines the force of the user grip through an Arduino-based system design using portable low-cost electromyography (EMG) sensors. Using this system, a visual illusion-based pseudo-haptic interface is designed to maximize presence in virtual reality. This involves processes that use a grasping illusion to enable the user to quickly become familiar with the system when tactile sensation is excluded, which maximizes immersion. Based on this process, an immersive virtual reality application is produced to survey and analyze user presence for the provided hand grip. Finally, the positive experience and improved presence for hand grip in immersive virtual reality are statistically analyzed and verified through user surveys.